Persepsi Penonton terhadap Interaksi Bahasa Isyarat dan Verbal dalam Drama Twinkling Watermelon - Anhar, Anhar; Aura May Safira; Aura Natasya Nur Putri; Zahra Anggraeni (Lembaga Intelektual Muda (LIM) Maluku, 2024)
Communication is the process of conveying information between two or more parties, encompassing both verbal and non-verbal communication. In the entertainment industry, verbal communication often takes center stage; however, recently, sign language as a form of non-verbal communication has gained increasing appreciation. Sign language is not only used by the deaf community but has also become a symbol of diversity. This research aims to analyze audience perceptions of the use of sign language and verbal communication in the drama Twinkling Watermelon. This study is categorized as qualitative descriptive research. Qualitative research as a particular tradition in social sciences that fundamentally relies on observing humans in their own environment and interacting with them in their own language and terminology. The research techniques utilized include observation, analysis, and documentation in the form of images from scenes in Twinkling Watermelon. The results indicate that viewers hold a positive view of sign language, perceiving it as enhancing awareness of the importance of inclusivity. The use of sign language in this drama underscores that deafness is not a deficiency, but rather a difference that deserves respect. This drama inspires viewers to be more open-minded and interested in learning sign language